The Impact of Perceived AI Adoption and Skill Preparedness on University Students’ Perceptions of Future Job Market Dynamic - Mohsin, Ainul Mohsein Binti Abdul; Mathur, Garima; Hairudin, Nor Amni Safiya Binti Nor; Ng, Shin Yan; Mazlan, Nur Aina Batrisyia Binti; Bakar, Nur Aneesa Sofea Binti Abu; Bhadouria, Pratiksha; Kee, Daisy Mui Hung (Advances in Global Economics and Business Journal, 2025)
The rapid adoption of Artificial Intelligence (AI) is transforming industries and redefining the global job market. In Malaysia, university students preparing to enter the workforce face growing uncertainty about how AI will impact their future careers. While AI brings opportunities for innovation and job creation, it also introduces challenges such as skill gaps, job displacement, and the need for continuous adaptation. According to the World Economic Forum (2023), an estimated 44% of workers’ skills will be disrupted within the next five years due to technological changes, emphasizing the urgency for future talent to be prepared. However, limited research has explored how university students perceive AI’s impact on employment and whether they feel equipped to meet the demands of this evolving landscape. This study aims to examine the relationship between perceived AI adoption and perceived skill preparedness on students’ perceptions of future job market dynamics. Using a quantitative approach, this study provides insights to inform curriculum design, career services, and workforce development strategies that align with the realities of an AI-integrated economy.